A New Approach to Bauxite Residue Dry Stacking: Utilizing Ciba® RHEOMAX™ ETD Technology - Kaiser, L.K.; Lamperd, J.W.; Loan, C.; Cooling, D.J. (Paste 2006: Proceedings of the Ninth International Seminar on Paste and Thickened Tailings, 2006)
Most mineral tailings are transported as slurry via a pipeline to a designated storage area. In principle, the aims of above ground tailings storage are to contain the tailings, consolidate these tailings to maximise storage efficiencies, aid rehabilitation, and maximise water recovery via efficient drainage and decant systems. Recent advances in tailings management have focussed on thickening of the tailings prior to deposition in the storage area to aid both consolidation and water recovery (Jewell et al, 2003). This is commonly referred to as “thickened tailings disposal” or “sloped deposition”. These systems rely on thickened slurry, which can be deposited in relatively thin layers on a sloped bed, allowing consolidation via both gravity drainage and solar drying. Over the past decade, significant advances have been made in the technology associated with thickening dilute slurries (Arbuthnot et al., 2005; Crozier et al., 2005). Thickeners have become more efficient and flocculants more effective. These advances have aided the development of thickened tailings disposal, making the process more affordable. Many new tailings storage facilities are now adapting the process to their specific needs. Ciba Specialty Chemicals has developed a range of rheology modifying products, which could play an important role in this type of tailings management process. These products modify the surface properties of the tailings when added to a slurry at point of discharge. The application known as Ciba® RHEOMAX™ ETD technology has been investigated on a range mineral of ore types at both laboratory and operational scale. Alcoa World Alumina Australia (Alcoa) currently produces bauxite tailings (referred to as residues), which are separated into coarse and fine fractions by cyclones. The coarse sand fraction is used for drainage layers, perimeter embankments, and final capping of the storage areas. The fine mud fraction is stored via a method of thickened residue disposal called “dry stacking”. This utilises a large diameter super thickener to dewater the fine residue, producing a high density underflow slurry of around 45 to 50% solids w/w. The thickened residue slurry is pumped to one of a number of drying beds and deposited in layers of up to 0.5m in depth. The yield stress of the mud and the slope of the bed are designed to allow for an even distribution of slurry across the bed. Paste2006–R.J.Jewell,S.Lawson,P.Newman(eds) ©2006AustralianCentreforGeomechanics,Perth,ISBN0-9756756-5-6 Paste2006,Limerick,Ireland 57 The fine residue dewaters through a combination of drainage and evaporative drying to a final dry density of around 70% solids w/w. Alcoa also routinely plough the mud with machinery to speed up the rate of moisture loss to evaporation and reduce the dusting potential from the drying beds. This process, sometimes referred to as “mud farming”, is generally done using a swamp dozer or amphirol (Cooling et al., 2002). This paper provides an overview of testing with Ciba® RHEOMAXTM ETD technology at Alcoa World Alumina Australia’s Western Australian refineries, and describes how this rheology modifier might be used to enhance the current storage processes.